TRAINING OF PERSONNEL IN BASKETBALL - Shodiyev Ergashali Qudratshoyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article allows you to master professional pedagogical knowledge, skills and skills related to physical education and sports vocabulary. It forms the Professional Scientific and pedagogical and organizational skills necessary for future personnel in educational institutions, physical education and sports organizations.